Life table and demographic parameters of bactrocera dorsalis reared on mango (Mangifera indica L.) - Mohamed, Salmah; Roseli, Marina; Sajili, Mohammad Hailmi; Adam, Nur Azura (Faisalabad Innovative Scientific Information & Services Network, 2019)
Survivorship from egg to adult emergence and fecundity from three cohorts of Oriental fruit fly, Batrocera dorsalis eggs on mango (Mangifera indica L.) were studied under laboratory conditions (28 ± 2 o C, 70-80% RH and 12:12h photoperiod). The life table showed that the survivorship of B. dorsalis falls in Type III with about 22.33% of the eggs successfully reached adult stage. The highest mortality recorded was in the 1 st instar larvae (48.59%) with k-value of 0.29 indicated that is the key factor regulating the population size of B. dorsalis. The sex ratio (proportion of female to male) was 1.09:1. The maximum life span of female was 50 days and the trend of oviposition showed a peak at about the 26 th day of female life span. Age specific fecundity (mx) showed the earliest egg laying on day 35 and the last female died on day 69. The female laid on average 410.0±61.22 eggs. The intrinsic rate of natural increase (rm) was 0.06 per female per day with mean generation time (Tc) of 46.39 days. The net reproductive rate (Ro) was 13.68 female offspring per female and the population of doubling time occurred within 12.38 days. This showed that the population of B. dorsalis has rapid buildup in short period of time.